COVID-19 Pandemic: Past, present and future - Behailu Assefa (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
COVID-19 is the emerged pandemic disease of mankind. This disease yet has no proven therapy. Measures like the use of a vaccine, chemical spray, disinfectants, antiseptics, and supportive therapies could help control this disease that is caused by a coronavirus. Further effective control and prevention measures are urgently demanded to save the life of billions of the world's human population. Especially having effective, and affordable vaccine that can be supplied as per its demand to all humankind is the priority at present.